Madagascar : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This paper analyzes the recent economic developments in Madagascar under the new Poverty Reduction and Growth Facility Arrangement. It highlights the production, income, and overall fiscal developments; discusses various measures to simplify the tax system, improve tax and customs administration; and tighten the expenditure management of the country. The paper provides a detailed study of the monetary developments, structure of the financial sector, balance of payments, external debt, and structural reforms of the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet